Pengaruh Pemberian Madu Terhadap Berat Badan Dan Kadar Malondialdehyd Pada Ibu Hamil Dengan Anemia - Astuti, Astuti; Asli, Kartika; Asrida, Asrida; Erviany, Nunung; Khair, Ummul (Jurnal Keperawatan Muhammadiyah, 2021)
Honey contains complex nutrients including vitamins A, C, E, B and flavonoids which play a role in suppressing oxidative stress. This study aimed to determine the effect of honey and Fe on body weight and malondialdehyde (MDA) levels of anemia pregnant women. The type of this study was quasi-experimental with the pretest-posttest design. Data analysis using paired t-test and independent samples test. After implementation the average value of the intervention group was 2.30 ± 0.50 while the average value of the control group was 2.00 ± 0.20 which showed that there was an effect of giving honey + Fe and Fe to the weight of anemic pregnant women. Whereas the statistical test results of the independent samples test showed p> 0.05 (p = 0.307) which means that there was no significant difference between the administration of honey + Fe (intervention) and Fe (control). In the melondialdehyde (MDA) variable there was a decrease in the intervention group by 8.86 ± 2.78 with the paired t-test obtained p value 0.002, this indicates there is an effect of giving honey + Fe to malondialdehyde (MDA) levels. The average value in the control group was 0.92 ± 0.07 with the paired t-test p value of 0.653 indicating no effect of Fe on Melondialdehyde (MDA) levels. Based on the test of the independent samples test obtained p value 0.004 (α <0.05). Conclusion: administration of honey + Fe effectively reduces malondialdehyde (MDA) levels and increases the weight of anemic pregnant women.